Attitudinal Factors in Hindering Community and Service Design Development in Suburban Village, Sarawak - Azaini, Manaf; Siti Shukhaila, Shaharuddin; Louis Laja, Unggah; Lee, SungPil (2018)
In developing countries, pockets of extreme poverty still exist. This research established the service design development in improving the livelihood of the suburban village in Kuching Sarawak. The team from UNIMAS and Non-governmental organization identified executed various projects including improving economic and sustainable the livelihood of the people in the suburban village. The research discovered attitude determinants which based commitment, anticipation, and feedback from the villagers. The project selected 7 participants with home-made food products to range from cakes, chips, biscuits, and frozen food. The participants then exposed with marketing skills, includes food preparation process and packaging design enhancement. Based on the results, the research distinguished 6 attitude avoidances, and it is recommended in selecting villagers with the right attitude to anticipate future entrepreneurship development. In conclusion in executing their livelihood projects, the education level of participants is vital, to enhance their own product. The necessity of education is crucial to eradicating poverty among villagers.